Burden of non-motor symptoms in unclear parkinsonism and tremor: A study with [I-123]FP-CIT SPECT - Elina Jaakkola; Juho Joutsa; Elina Mäkinen; Tommi Noponen; Miia Pitkonen; Reeta Levo; Tuomas Mertsalmi; Filip Scheperjans; Valtteri Kaasinen (ELSEVIER, 2022)
Background: Non-motor symptoms (NMSs) are clearly more prevalent in Parkinson's disease (PD) patients compared to healthy individuals. However, NMSs are also common in the elderly and other neurological conditions, and thus, it is not known whether NMSs could be used to differentiate PD from parkinsonism/tremor without dopamine deficiency.Methods: We prospectively evaluated NMSs immediately before brain dopamine transporter (DAT) [I-123]FP-CIT SPECT scanning in 193 patients with unclear parkinsonism/tremor. According to the clinical follow-up and imaging results, 84 patients had PD. NMSs and their correlations with striatal DAT binding were investigated in PD patients and in parkinsonism/tremor patients with normal dopamine function.Results: Total NMS burden, anxiety or depression did not differ between PD patients and patients with normal DAT binding. DAT-normal patients reported more perception-related (p = 0.045) and attention/memory-related NMSs than PD patients (p < 0.001). Total NMS score did not correlate with striatal DAT binding in either group.Conclusions: In clinically uncertain cases, the total NMS burden cannot be used as a tool in distinguishing PD patients from patients with non-dopaminergic parkinsonism/tremor. Clinical screening of NMSs appears equally important in all patients with parkinsonism.